2022
DOI: 10.2478/zireb-2022-0001
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Capital Flows and Human Development in Developing Countries: Does Institutional Quality Matter?

Abstract: The impact of foreign capital on human development has been at best ambiguous, while that of institutions is undoubtedly favorable. That said, the way foreign capital relates to human development may be affected by the quality of institutions. This paper assesses this very phenomenon in 65 developing countries over the time period 1984-2014. In this regard, this study incorporates three indicators of human development namely, per capita income (PCI), Secondary School Enrollment (SSE) and Life Expectancy (LE). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Another strand of empirical studies reported that institutions have significant positive effect on human development (Balcerzak and Pietrzak, 2017;Ejuvbekpokpo, 2017;Hashem, 2019;Kamalu and Wan Ibrahim, 2022;Muro and Tridico, 2008). The study of Kouadio and Gakpa (2022) show that quality institutions have negative effect on inequality and poverty, while Ali et al (2020) found that institutions plays a significant role in enhancing positive effect of official development assistance on human development. However, a study by Ejemeyovwi et al (2018) reported that ICT development have negative impact on human development, while Mardanov (2020) found that institutions have positive insignificant effect on human development in 22 transitional economies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strand of empirical studies reported that institutions have significant positive effect on human development (Balcerzak and Pietrzak, 2017;Ejuvbekpokpo, 2017;Hashem, 2019;Kamalu and Wan Ibrahim, 2022;Muro and Tridico, 2008). The study of Kouadio and Gakpa (2022) show that quality institutions have negative effect on inequality and poverty, while Ali et al (2020) found that institutions plays a significant role in enhancing positive effect of official development assistance on human development. However, a study by Ejemeyovwi et al (2018) reported that ICT development have negative impact on human development, while Mardanov (2020) found that institutions have positive insignificant effect on human development in 22 transitional economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, efficient allocation of scarce resources is one of the factors that greatly improve living conditions Strong institutional environment control corruption, curb mismanagement, protect property rights, rule of law and implement quality regulations, which have strong correlation with increasing human development (Brady, 2019). It is been argued that institutions determine almost everything in a society, hence, the difference between GDP growth is determine by the level of quality institutions in the society (Ali et al, 2020;Kamalu and Ibrahim, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nigeria alone has witnessed about 180% increase in the number of undernourished people over the last decade as reported in the 2019 Africa regional overview of food security and nutrition. Furthermore, weak institutional capacity in many SSA countries undermines efforts to achieve optimal level of food and nutrition security as they significantly impact on economic development [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While factors such as climate change affect countries globally, countries with limited economic growth struggle to achieve significant development targets and food self-sufficiency without inputs from foreign aid and other capital flows. Studies on the impact of foreign capital flows in SSA, mainly in connection with foreign direct investment, official development assistance, remittances, and portfolio equity, have largely focused on developmental indicators such as human capital development, economic growth, and employment among others [ 6 , 10 , 11 ]. However, the impact of foreign capital flows on food and nutrition security has not received significant attention and this needs to improve.…”
Section: Introductionmentioning
confidence: 99%